SERPIN-A3 is associated with persistent albuminuria in adolescents with secondary podocytopathy, in a region with high prevalence of chronic kidney disease of unknown origin - Leslie P. Zúñiga-Macías; Ricardo E. Ramírez-Orozco; Francisco J. Avelar-González; Rosalba Pérez-Villalva; Norma A. Bobadilla; José M. Arreola-Guerra (Permanyer, 2023)
Background: The state of Aguascalientes, Mexico, has been recognized as a chronic kidney disease hotspot. Screening studies have revealed a high prevalence of persistent albuminuria (pA), histologically characterized by glomerulomegaly, and incomplete podocyte fusion, probably associated with oligonephrony. To date, urinary biomarkers have not been explored in this population. Objective: The aim of the study was to identify the presence of potential biomarkers of early renal injury in patients with pA (pACR) and that correspond with the characteristic nephropathy profile that prevails in this entity. Methods: This is a crosssectional, analytical, and comparative study. Four groups were recruited: adolescents aged 10-17 years with pACR, isolated albuminuria (iACR), no albuminuria (negative control), and adults with biopsy-confirmed glomerulopathy (positive control). Urinary excretion of SerpinA3, heat-shock protein-72 (HSP-72), podocalyxin (PCX), and nephrin was evaluated in urine samples. SerpinA3 and HSP-72 were analyzed by Western blot, and PCX and nephrin were quantified by enzyme-linked immunosorbent assay. Results: The mean GFR in the pACR group was 113.4 mL/min/1.73m2 and differed significantly only from that of the positive control group (65.1 mL/min/1.73m2). The mean albuminuria value in the pACR group was 48.9 mg/g. SerpinA3 concentration differed between groups (0.08 vs. 0.25 ng/mL, p < 0.001): it was significantly higher in the pACR group compared to the negative controls (p = 0.037). Conclusion: SerpinA3 was significantly associated with pA and could become a biomarker of early kidney injury. Further investigations are required to determine whether SerpinA3 precedes the development of albuminuria and its pathogenic role.